Identification of 6ω-cyclohexyl-2-(phenylamino carbonylmethylthio)pyrimidin-4(3H)-ones targeting the ZIKV NS5 RNA dependent RNA polymerase - Zhou, Guang-Feng; Xie, Cong-Qiang; Xue, Jian-Xia; Wang, Jing-Bo; Yang, Yu-Zhuo; Zheng, Chang-Bo; Luo, Rong-Hua; Yang, Ren-Hua; Chen, Wen; Yang, Liu-Meng; Wang, Yue-Ping; Zhang, Hong-Bin; et al. (Frontiers in Chemistry, 2022)
Zika virus (ZIKV), a mosquito-borne flavivirus, is a global health concern because of its association with severe neurological disorders such as neonatal microcephaly and adult Guillain-Barre syndrome. Although many efforts have been made to combat ZIKV infection, there is currently no approved vaccines or antiviral drugs available and there is an urgent need to develop effective anti-ZIKV agents. In this study, 26 acetylarylamine-S-DACOs derivatives were prepared, and eight of them were found to have inhibitory activity against Zika virus. Among these substances, 2-[(4-cyclohexyl-5-ethyl-6-oxo-1,6-dihydropyrimidin-2-yl)thio]-N-(3,5-difluorophenyl)acetamide (4w) with the best anti-ZIKV activity was selected for in-depth study of antiviral activity and mechanism of action. Here, we discovered 4w targeted on the ZIKV NS5 RNA -dependent RNA polymerase (RdRp), which exhibited good in vitro antiviral activity without cell species specificity, both at the protein level and at the RNA level can significantly inhibit ZIKV replication. Preliminary molecular docking studies showed that 4w preferentially binds to the palm region of NS5A RdRp through hydrogen bonding with residues such as LYS468, PHE466, GLU465, and GLY467. ZIKV NS5 RdRp enzyme activity experiment showed that 4w could directly inhibit ZIKV RdRp activity with EC50 = 11.38 ± 0.51 μM. In antiviral activity studies, 4w was found to inhibit ZIKV RNA replication with EC50 = 6.87 ± 1.21 μM. ZIKV-induced plaque formation was inhibited with EC50 = 7.65 ± 0.31 μM. In conclusion, our study disclosed that acetylarylamine-S-DACOs is a new active scaffolds against ZIKV, among which compound 4w was proved to be a potent novel anti-ZIKV compound target ZIKV RdRp protein. These promising results provide a future prospective for the development of ZIKV RdRp inhibitors.